Effects of adjuvants for human use in systemic lupus erythematosus (SLE)-prone (New Zealand black/New Zealand white) F1 mice. (3rd December 2013) - Favoino, E; Favia, E I; Digiglio, L; Racanelli, V; Shoenfeld, Y; Perosa, F
Summary: The safety of four different adjuvants was assessed in lupus-prone New Zealand black/New Zealand white (BW)F1 mice. Four groups of mice were injected intraperitoneally with incomplete Freund's adjuvant (IFA), complete Freund's adjuvant (CFA), squalene (SQU) or aluminium hydroxide (ALU). An additional group received plain phosphate-buffered saline (PBS) (UNT group). Mice were primed at week 9 and boosted every other week up to week 15. Proteinuria became detectable at weeks 17 (IFA group), 24 (CFA group), 28 (SQU and ALU groups) and 32 (UNT group). Different mean values were obtained among the groups from weeks 17 to 21 [week 17: one-way analysis of variance (anova ) P  = 0·016; weeks 18 and 19: P  = 0·048; weeks 20 and 21: P  = 0·013] being higher in the IFA group than the others [Tukey's honestly significant difference (HSD) post-test P  < 0·05]. No differences in anti-DNA antibody levels were observed among groups. Anti-RNP/Sm antibody developed at week 19 in only one CFA-treated mouse. Mean mouse weight at week 18 was lower in the ALU group than the IFA (Tukey's HSD post-test P  = 0·04), CFA ( P  = 0·01) and SQU ( P  < 0·0001) groups, while the mean weight in the SQU group was higher than in the IFA ( P  = 0·009), CFA ( P  = 0·013) and UNT ( P  = 0·005) groups. The ALU group weight decreased by almost half between weeks 29 and 31, indicating some toxic effect of ALU in the late post-immunization period. Thus, SQU was the least toxic adjuvant as it did not (i) accelerate proteinuria onset compared to IFA; (ii) induce toxicity compared to ALU or (iii) elicit anti-RNP/Sm autoantibody, as occurred in the CFA group.